Modernisasi Kurikulum Pendidikan Islam (Studi Atas Pemikiran Azyumardi Azra) - Imam Nur Hukum (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Modernization is an effort to change in order to aligned with contemporary demands and needs. The curriculum of Islamic education is important to be modernized so that the curriculum is contextual so as to give an answer to the demands and needs of the students according to era. One of the underlying need for the modernization of Islamic education is characterized curriculum of Islamic education is still a â€œtraditionalistâ€ (despite the fact that not all of them), with one feature of the persistence of the dichotomization of science (materials) of Islamic education, or tend to concerned with the general materials beyond religious materials. Azyumardi Azra, as a prominent reform of Islamic education in Indonesia, declared that the rapid development of science and technology demands Islamic education to be responsive and up to date, so that Muslims continue to survive and compete with advanced nations. For Azyumardi, â€œmaking stepchildâ€ science and technology is an attitude that will bring a decline, backwardness, and underdevelopment in the global competition which is getting tougher. Therefore according to Azyumardi, the integration of science (general and religious) in Islamic education is the thing that should be done as a solution to promote Islamic education so as able to compete and beat the forefront. Key words: Modernization, Curriculum, Islamic Education